Pengembangan Kapasitas Pegawai Badan Layanan Umum Daerah Non Pegawai Negeri Sipil (Studi di RSUD Kabupaten Sidoarjo) - Satriya Wahyudi, Ageng; Domai, Tjahjanulin; Setyowati, Endah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
Capacity Building of Local Public Service Instance Employees for Non CivilServants (Case Study in Public Hospital of Sidoarjo). Capacity building through education has not yet to be implemented affectively, especially for Non Civil Servants employees because of the regulations. The Regulations which is indicates that only the Civil Servants Employees who have the rights to obtain education facilities are covered by Government. While for Non Civil Servants employees can obtain rights equal to using financial from the Public Hospital of Sidoarjo. Capacity building also constrained in stage of training evaluation; there is the evaluation of benefits applies has not been able to run properly.